Informativity, topicality, and speech cost: comparing models of speakers' choices of referring expressions. Issue 8 (14th September 2021) - Orita, Naho; Vornov, Eliana; Feldman, Naomi H.
ABSTRACT: This study formalizes and compares two major hypotheses in speakers' choices of referring expressions: the topicality model that chooses a form based on the topicality of the referent, and the rational model that chooses a form based on the informativity of the form and its speech cost. Simulations suggest that both the topicality of the referent and the informativity of the word are important to consider in speakers' choices of reference forms, while a speech cost metric that prefers shorter forms may not be.